Feed consumed by pregnant sows confined in groups - Costa, Valdomiro; Ferreira, Aloízio Soares; Gomes, Paulo Cezar; Fialho, Elias Tadeu; Freitas, Alfredo Ribeiro de (Pesquisa Agropecuaria Brasileira, 2014)
In order to evaluate the reproductive performance of sows under different alimentar regimens, 48 Large White gilts were utilized. They were subjected to four different rations during three consecutive reproductive cicle. These rations consisted of 2; 1.8; 1.6 and 1.4 kg of food per day, during gestation and "ad libitum" during lactation. During the gestation period, the sows were kept confined in groups of six per pen and they received the feed through individual feeders. Piglets wore weaned with 35 days of age. Each increase of feed consumption in the gestation period resulted in a linear increase in the weight gain of the sows (P<0,001). The weight of sows during lactation decreased linearly (P<0,01) with the increased consumption of feed during gestation. Biggest litters were observed in the second and third reproductive cicle. Nevertheless, no differences were observed among treatments in regard to the number of alive and death born piglets. Litters from sows kept under 2 kg of feed per day showed more weighty litters at birth and at the weaning period than those kept under 1.6 kg of feed. Mortality rate was higher among piglets from the third reproductive cicle than that from the second and first ones. Nevertheless, mortality rate was similar among litters from all treatments.